2009
DOI: 10.1111/j.1468-3083.2008.03070.x
|View full text |Cite
|
Sign up to set email alerts
|

Punctate leucoderma after melasma treatment using 1064‐nm Q‐switched Nd:YAG laser with low pulse energy

Abstract: diarrhea. Alopecia, oedema, facial erythematous rash, hair depigmentation, stomatitis, xerosis and subungueal splinter haemorrhages have been reported. Two cases of inflammation of actinic keratoses and a case of erythema multiforme subsequent to therapy with sorafenib have also been described. 3,4 We have presented a particular case which represents a unique form of dermatologic toxicity to sorafenib that has not previously been described in the literature.The use of tyrosine kinase inhibitor may result in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 5 publications
3
63
0
1
Order By: Relevance
“…Notwithstanding, the possibility of rebound hyperpigmentation (RH) and punctate leukoderma have since been found to be the major concerns for this treatment. 7,8 Studies have shown that the skin behaves like a semiconductor. 9 When emitted on the skin, radiofrequency (RF) elicits epidermal and dermal heating.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, the possibility of rebound hyperpigmentation (RH) and punctate leukoderma have since been found to be the major concerns for this treatment. 7,8 Studies have shown that the skin behaves like a semiconductor. 9 When emitted on the skin, radiofrequency (RF) elicits epidermal and dermal heating.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al 10 reported some interesting results. This study focused on punctate leukoderma developing after laser toning treatments performed in 259 patients.…”
Section: Studies That Warn Against Laser Toning Emphasize the Risk Ofmentioning
confidence: 74%
“…In this study, the parameters were maintained the same as the authors' previous study, except for the fluence which was lowered to about 50-60% of that used in the previous study. 9,10 It is interesting to note that the rate of hypopigmentation is much lower in this study. Although the fluence was lower than the previous studies, it was still higher than the levels normally used in today's clinical practice (2.0 J/cm 2 or less).…”
Section: Studies That Warn Against Laser Toning Emphasize the Risk Ofmentioning
confidence: 82%
“…Although subthermolytic Q-switched 1064nm Nd Yag laser therapy has shown promising results, this treatment would require multiple sessions on a weekly basis, which would burden the patients (16,17). In addition, there are some reports of confetti-like hypopigmentation occurring after multiple treatment sessions (18,19). In general, epidermal type melasma respond well to these conventional treatment (20).…”
Section: Introductionmentioning
confidence: 99%